THE POTENTIAL OF BRAZILIAN AGRICULTURE FOR REDUCING GREENHOUSE GASES: AN ANALYSIS OF COFFEE GROWING AND LESSONS FOR COP30 - de Freitas Santos, Jamilsen; Madeira Nogueira, Jorge (RP3 - Revista de Pesquisa em Políticas Públicas, 2025)
Abstract This article analyzes the potential of Brazilian coffee production to contribute to national greenhouse gas (GHG) mitigation targets under the recently established Brazilian Emissions Trading System (SBCE). The methodology uses a scenario analysis, based on census data, to assess how transaction costs determine a minimum viable area for market participation, impacting the sector's aggregate potential. The results reveal a critical duality: although there is a vast theoretical mitigation potential, estimated at 13 million tons of CO₂eq, its realization is severely limited by economic barriers that could prevent up to 67% of this total from being realized. The high costs of certifying and monitoring carbon credits exclude most coffee growers, especially family farmers, which constitute the structural foundation of the sector. We conclude that the effectiveness of the carbon market as a climate policy in Brazil depends on institutional innovations—such as collective certification through cooperatives and the development of low-cost monitoring technologies—to reduce transaction costs. Additionally, it is recommended that voluntary instruments, such as carbon-neutral coffee labeling, be promoted to encourage the adoption of good agricultural practices in an inclusive manner and achieve Brazil's GHG reduction targets. Such measures are crucial to ensuring broad and equitable participation of rural producers, aligning the market instrument with the reality of national agriculture.